Profile of dog bite cases reporting to ARV OPD of a tertiary care hospital - Subramanya, Saurabha Urmi; Kembhavi, Ravindra S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Animal bites pose a major public health problem in children and adults worldwide. Rabies is a viral zoonosis caused by bite of a rabid dog that occurs in >100 countries and territories. India accounts for 60% of all the world burden of rabies related deaths. The objective of the present study is to analyse the profile of dog bite victims reporting to ARV OPD of a tertiary care hospital. Methods: This was a cross-sectional study conducted in the ARV OPD of a tertiary care hospital. A total of 228 victims of dog bite were interviewed. They were selected using systematic random sampling technique. Analysis of data obtained was done using SPSS. Results: Majority of the participants belonged to the age group 20-30 years. The proportion of male was higher than female. Most of the victims had suffered category II type of dog bite (66.2%). A statistically significant association was seen between age group and nature of dog bite, sex of victim and type of dog, type of dog and category of dog bite and the category of bite and history of dog biting other individuals. Conclusions: The burden of dog bite seems to be borne by the economically productive age group. All individuals need to be educated on how to behave around animals so that they can avoid animal bite.